Ballistic resistance of high-strength armor steel against ogive-nosed projectile impact. (February 2023) - Cheng, Y.H.; Wu, H.; Jiang, P.F.; Fang, Q.
Abstract: The advanced high-strength armor steel with the superior strength-to-weight ratio can extremely improve the ballistic resistance and mobility of military equipment and structures. Aiming to assess the ballistic resistance including the ballistic limit and failure modes of two types of advanced high-strength armor steels, the projectile perforation test and numerical simulations were conducted. Firstly, ten shots of 15 mm-caliber ogive-nosed projectile perforation test were performed under the initial impact velocities of 164–428 m/s. The failure mode and out-of-plane displacement (OPD) response of target plate were recorded by utilizing the high-speed 3D digital image correlation system. Then, the classical finite element (FE) and mesh-free Smoothed Particle Galerkin (SPG) methods were adopted to conduct the numerical simulations, respectively. The predicted residual velocities of projectile were compared with the test data to verify the accuracy of the calibrated constitutive model parameters and numerical analysis approaches. By further comparing the failure modes and OPD–time histories of target, it was drawn that the FE method is preferable to reproduce the failure mode of target, while the SPG method is recommended to quickly predict the residual velocity of projectile. Finally, by adopting the validated numerical analysis approach, the residual velocities for two types of high-strength armor steels under the initial impact velocity range of 150–600 m/s were obtained. The reliabilities of the existing seven analytical models in predicting the ballistic limit and residual velocity for high-strength armor steels were further evaluated. Highlights: Projectile perforation test on two types of high-strength armor steels was conducted. Ballistic resistance of armor steel against ogive-nosed projectile impact is assessed. Simulation approaches are verified by both dynamic behaviors of projectile and target. Applicability of FE and SPG methods in predicting ballistic resistance is evaluated. Reliabilities of terminal ballistic analytical models for armor steel are examined.